1999
DOI: 10.1164/ajrccm.160.1.9809140
|View full text |Cite
|
Sign up to set email alerts
|

Increased 8-Isoprostane, a Marker of Oxidative Stress, in Exhaled Condensate of Asthma Patients

Abstract: Oxidative stress has an important role in the pathogenesis of asthma. 8-Isoprostane is a prostaglandin (PG)-F2-like compound belonging to the F2 isoprostane class that is produced in vivo by the free radical-catalyzed peroxidation of arachidonic acid. 8-Isoprostane is a biomarker of oxidative stress, and its concentration is increased in the bronchoalveolar lavage fluid of patients with interstitial lung diseases. We measured 8-isoprostane concentrations in exhaled breath condensate in healthy subjects and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
356
5
32

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(414 citation statements)
references
References 31 publications
21
356
5
32
Order By: Relevance
“…Biomarkers are originated from lower airways, but there is the possibility of saliva, upper respiratory tract contamination. To date, changes of biochemical markers of inflammation and oxidative stress have been most extensively investigated in patients with asthma (38,39), COPD (40,41), cystic fibrosis (42,43), and lung carcinoma (44) and less extensively in other pulmonary diseases (45). There is a general opinion that profiles of different analytes in EBC could be chosen in the future to help in the differential diagnosis of pulmonary diseases (16).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers are originated from lower airways, but there is the possibility of saliva, upper respiratory tract contamination. To date, changes of biochemical markers of inflammation and oxidative stress have been most extensively investigated in patients with asthma (38,39), COPD (40,41), cystic fibrosis (42,43), and lung carcinoma (44) and less extensively in other pulmonary diseases (45). There is a general opinion that profiles of different analytes in EBC could be chosen in the future to help in the differential diagnosis of pulmonary diseases (16).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is also increased in patients with severe asthma and during exacerbations [99][100][101], such that a reduction in HDAC may also account for the reduced responsiveness to corticosteroids in these patients and the relative unresponsiveness of acute exacerbation of asthma to corticosteroids.…”
Section: Smoking Asthmaticsmentioning
confidence: 99%
“…Firstly, the inflammatory process results in the generation of oxygen free radicals, and antioxidant defence systems are important in controlling inflammation (Greene, 1999). Atopic diseases, in particular asthma and atopic dermatitis, are characterized by increased oxidative stress (Montuschi et al, 1999;Omata et al, 2001). Second, there is evidence that a low antioxidant intake may be associated with allergic symptoms; low vitamin C intake has been linked with wheezing (Bodner et al, 1999) and bronchial hyper-reactivity (Soutar et al, 1997) and an inverse association has been observed between dietary vitamin E intake and serum total IgE .…”
Section: Introductionmentioning
confidence: 99%